2005
DOI: 10.1158/1535-7163.mct-04-0196
|View full text |Cite
|
Sign up to set email alerts
|

p53 gene therapy of human osteosarcoma using a transferrin-modified cationic liposome

Abstract: Gene delivery via transferrin receptors, which are highly expressed by cancer cells, can be used to enhance the effectiveness of gene therapy for cancer. In this study, we examined the efficacy of p53 gene therapy in human osteosarcoma (HOSM-1) cells derived from the oral cavity using a cationic liposome supplemented with transferrin. HOSM-1 cells were exposed to transferrin-liposome-p53 in vitro, and the growth inhibition rate, expression of p53 and bax, and induction of apoptosis were measured 48 hours later… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(44 citation statements)
references
References 35 publications
0
43
0
Order By: Relevance
“…For cell-specific gene delivery, cell type-specific surface molecules and their antibodies would be useful, and a number of cell-specific gene delivery vectors have been developed (Germershaus, et al, 2006;Chiu, et al, 2004;Liu, et al, 2007). For cancer gene therapy, tumor suppressor genes such as p53 gene and suicide genes such as herpes simplex virus thymidine kinase gene were well studied; and those genes reported to suppress tumor growth by tumor specific gene delivery vector such as transferrin-modified cationic liposome (Nakase, et al, 2005;Neves, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…For cell-specific gene delivery, cell type-specific surface molecules and their antibodies would be useful, and a number of cell-specific gene delivery vectors have been developed (Germershaus, et al, 2006;Chiu, et al, 2004;Liu, et al, 2007). For cancer gene therapy, tumor suppressor genes such as p53 gene and suicide genes such as herpes simplex virus thymidine kinase gene were well studied; and those genes reported to suppress tumor growth by tumor specific gene delivery vector such as transferrin-modified cationic liposome (Nakase, et al, 2005;Neves, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The study by Nakase et al suggested that p-53 gene therapy via cationic liposome modification with transferrin is an effective strategy for the treatment of osteosarcoma. However, further research is required to improve the clinical efficacy (21). Immunotherapy has great potential for treating osteosarcomas, promising improved patient survival rates and quality of life (22).…”
Section: Discussionmentioning
confidence: 99%
“…Active targeting of tumor tissue by liposomes can be achieved by modifying the liposome with addition of a targeting ligand, such as an antibody and a peptide. [48][49][50][51] However, the problem with these systems is that the majority of the liposomes are still cleared by the reticuloendothelial system, resulting in short half-lives, low accumulation in tumor tissue, and unwanted deposition in the liver and spleen. To achieve a specific therapeutic effect, both a prolonged blood circulation time and an active tumortargeting effect are essential for an ideal drug delivery system.…”
Section: Discussionmentioning
confidence: 99%